Valuation of Mangrove Ecosystems to Income of Coastal Communities: An Overview of Economic Benefits in Sidodadi Village, Teluk Pandan District, Lampung - Imani Fatehah, Muhammad Aqsal (Politeknik Siber Cerdika Internasional, 2025)
This study aims to analyze the influence of mangrove ecosystems on the welfare of coastal communities, especially by reviewing its economic benefits in Sidodadi Village, Teluk Pandan Regency, Lampung. Mangrove forests play an important role in three main aspects: physical (protecting against abrasion and waves), biological (serving as a source of nutrients and spawning grounds for marine life), and economic (as a direct resource). The methodology used is a descriptive analysis using secondary data from literature studies. The Total Economic Value (TEV) approach, calculated by adding Direct Use Value (DUV) and Indirect Use Value (IUV), is used for economic valuation. The findings show that the direct use value (DUV) obtained by the community from firewood, shrimp, fish, and crab cultivation is IDR 1,571,507,000. Meanwhile, the indirect use value (IUV), which is the cost avoided from building a coastal protection structure, reached IDR 3,386,276,000. Thus, the Total Economic Value (TEV) of mangrove ecosystems in this region is IDR 4,844,198,500. In addition to its economic value, the existence of mangrove ecotourism also has a positive socio-economic impact, encouraging local communities to take advantage of new economic opportunities to improve their welfare.